Bibliometric analysis of publications trends on the terrorism issues in Indonesia - Gonda Yumitro; Rizki Febriani; Ali Roziqin; Anisa Indraningtyas (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. The issue of terrorism in Indonesia has been a challenge around the world, particularly in a country with the world's largest Muslim population. This study aims to evaluate the trend of publications on the issue of terrorism in Indonesia in the period starting from 1980 to 2022 through a bibliometric analysis. Data Collection Methods. Data were obtained from the Scopus database using the keywords "terrorism", "terrorist", "terror", and "Indonesia". Data Analysis. The VOSviewer data visualization was used as a data analysis tool to show the trends in publications on terrorism issues in Indonesia. Results and Discussion. The publication trend on terrorism in Indonesia significantly increased, with distribution countries dominated by Indonesia including authors, affiliates, and sponsors. In addition, publications on the issue of terrorism in Indonesia were widely written in journal articles, particularly in the field of social sciences. Conclusion. The issue of terrorism in Indonesia is dynamic. This research may be used to update the understanding of current terrorism issues in Indonesia, particularly from bibliometric analysis.